Experimental investigation of Versa Tyle GRP for solar thermal system. Issue 1 (2nd January 2021) - Abdellatif, Mawada; Baynes, Stephen; Osman, Yassin; Brady, Laurence; Cullen, Jeff; King, Derek
ABSTRACT: Solar thermal systems have encountered a high level of interest over the last ten years due to their low cost and convenience in reducing energy load for domestic hot water. This paper aimed to introduce a new panel's material (Versa Tyle GRP Tiles) for solar thermal system and a prototype was built in a small shed at a site in Liverpool (UK), in order to assess its performance. The experiment was run for 12 months for the purpose of collecting and analyzing thermal data in terms of heat capacity, solar energy, and solar fraction. To simulate the daily use of water consumption and provide realistic outputs, the system was emptying every day at different durations in order to investigate the recovery period of the temperatures. The results proved the feasibility and efficiency of the Versa Tyle GRP as the maximum recorded temperature on the tiles was 68°C, and 51°C for the hot water in July; while winter months recorded a maximum of 26°C for the hot water. The system achieved average solar fraction of 36.52–47.43% between May to September, while in the rest of the months in the year, average solar fraction of 2.95%-18.59% were detected.